Forensic and Legal Medicine State of the Art, Practical Applications and New Perspectives - Scendoni, Roberto; De Micco, Francesco (IntechOpen, 2023)
Forensic medicine is a scientific discipline characterized by continuous evolution due not only to progress in medical knowledge but also to changing juridical and social requirements. This book analyzes the state of the art and the most interesting lines of research in forensic medicine, laying the foundations to explore new perspectives in multiple disciplinary sectors. This book collects several themes to create a practical tool of knowledge for experts in the discipline as well as young and emerging researchers.